The potential of coconut shell powder (CSP) and coconut shell activated carbon (CSAC) composites as electromagnetic interference (EMI) absorbing material - Seok, Yew Been; Siti Nurbazilah, Ab. Jabal; Hoon, Wee Fwen (Malaysian Society of Analytical Sciences, 2016)
Agriculture waste is potentially useful as an alternative material to absorb and attenuate electromagnetic interference (EMI). This research highlights the use of coconut shell powder (CSP) and coconut shell activated carbon (CSAC) as raw materials with epoxy resin and amine hardener composite to absorb microwave signals over frequency of 1 – 8 GHz. In order to investigate the suitability of these raw materials as EMI absorbing material, carbon composition of the raw materials is determined through CHNS Elemental Analysis. The surface morphology of the raw materials in term of porosity is investigated by using TM3000 Scanning Electron Microscope (SEM). The complex permittivity of the composites is determined by using high temperature dielectric probe in conjunction with Network Analyzer. From the result, the Carbon% of CSP and CSAC is 46.70% and 84.28% respectively. In term of surface morphology, the surface porosity of CSP and CSAC is in the range of 2 µm and 1µm respectively. For the dielectric properties, the dielectric constant and the dielectric loss factor for CSP and CSAC is 4.5767 and 64.8307and 1.2144 and 13.8296 respectively. The materials more potentially useful as substitute materials for electromagnetic interference (EMI) absorbing are discussed.